Identifying the Bifunctional Mechanism in Alkaline Water Electrolysis by Lewis Pairs at the Single-Atom Scale - Jin, Hongqiang; Chen, Xiang; Da, Yumin; Fan, Lei; Jiang, Rui; Xiao, Yukun; Yao, Bingqing; He, Qian; Yu, Yu; Chen, Wei (Journal of the American Chemical Society, 2025)
The bifunctional mechanism, involving multiactive compositions to simultaneously dissociate water molecules and optimize intermediate adsorption, has been widely used in the design of catalysts to boost water electrolysis for sustainable hydrogen energy production but remains debatable due to difficulties in accurately identifying the reaction process. Here, we proposed the concept of well-defined Lewis pairs in single-atom catalysts, with a unique acid–base nature, to comprehensively understand the exact role of multiactive compositions in an alkaline hydrogen evolution reaction. By facilely adjusting active moieties, the induced synergistic effect between Lewis pairs (M–P/S/Cr pairs, M = Ru, Ir, Pt) can significantly facilitate the cleavage of the H–OH bond and accelerate the removal of intermediates, thereby switching the rate-determining step from the Volmer step to the Heyrovsky step. Moreover, the representative Ru–P Lewis pairs deliver an impressive 266 h durability at a high industrial current density of 2 A cm–2 without activity decay in anion-exchange membrane water electrolysis, and the concept can be extended to modify commercial noble-metal-based catalysts for performance enhancement. This work not only sheds light on the important effect of the bifunctional mechanism in alkaline water electrolysis at the single-atom scale but also offers a universal descriptor for the rational design of advanced catalysts.